2009
DOI: 10.1111/j.1754-9485.2009.02042.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of radiotherapy to treat life‐threatening Kasabach–Merritt syndrome

Abstract: SummaryKasabach-Merritt syndrome involves thrombocytopenia, which is usually severe, in association with haemangiomata. We describe two newborn infants who developed life-threatening Kasabach-Merritt syndrome but who were successfully treated. Both had failed to respond adequately to corticosteroids and a-interferon. They subsequently received emergency radiotherapy. Both patients had an improvement in their platelet counts. The first infant's haemangioma gradually faded during the first 3 years of life, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Radiation therapy was curative in the initial case of KMP (Kasabach & Merritt, ) and has proven effective in many other case reports and small series since (El‐Dessouky et al , ; Leong & Bydder, ). In a series of 28 patients, when used in combination with steroids, there was a 75% response rate, with no radiation‐induced side effects over a median follow‐up of more than 6 years (Shin et al , ).…”
Section: Mechanical Options and Radiotherapymentioning
confidence: 99%
“…Radiation therapy was curative in the initial case of KMP (Kasabach & Merritt, ) and has proven effective in many other case reports and small series since (El‐Dessouky et al , ; Leong & Bydder, ). In a series of 28 patients, when used in combination with steroids, there was a 75% response rate, with no radiation‐induced side effects over a median follow‐up of more than 6 years (Shin et al , ).…”
Section: Mechanical Options and Radiotherapymentioning
confidence: 99%
“…Historically, radiation therapy has been associated with multiple long-term side effects when used in pediatric population [60,100,[113][114][115][116] its use in adults has been more liberal. In a series of 28 patients, concurrent radiation and steroids demonstrated a 75% response rate, with no radiation-induced side effects over a median follow-up of more than 6 years [117]. With new advancements in radiotherapy, there is minimal radiation delivered to uninvolved organs and this can lead to more liberal use for adult population.…”
Section: Radiationmentioning
confidence: 99%
“…Although some small-cohort studies have reported no detection of cancer in response to radiation, 8,9 a retrospective study of 18 000 patients treated with radiotherapy for hemangioma during childhood noted a significantly increased dose-dependent risk of breast cancer, brain tumors, and bone tumors. 10 Therefore, Mitsuhashi et al 9 recommended that the total irradiation dose be kept as low as possible, not exceeding 10 Gy.…”
Section: Discussionmentioning
confidence: 99%